Interactions Between Natural Herbicides and Lipid Bilayers Mimicking the Plant Plasma Membrane - Lebecque, Simon; Lins, Laurence; Dayan, Franck E.; Fauconnier, Marie-Laure; Deleu, Magali (Frontiers in Plant Science, 2019)
Natural phytotoxic compounds could become an alternative to traditional herbicides in the framework of sustainable agriculture. Nonanoic acid, sarmentine and sorgoleone are such molecules extracted from plants and able to inhibit the growth of various plant species. However, their mode of action is not fully understood and despite clues indicating that they could affect the plant plasma membrane, molecular details of such phenomenon are lacking. In this paper, we investigate the interactions between those natural herbicides and artificial bilayers mimicking the plant plasma membrane. First, their ability to affect lipid order and fluidity is evaluated by means of fluorescence measurements. It appears that sorgoleone has a clear ordering effect on lipid bilayers, while nonanoic acid and sarmentine induce no or little change to these parameters. Then, a thermodynamic characterization of interactions of each compound with lipid vesicles is obtained with isothermal titration calorimetry, and their respective affinity for bilayers is found to be ranked as follows: sorgoleone > sarmentine > nonanoic acid. Finally, molecular dynamics simulations give molecular details about the location of each compound within a lipid bilayer and confirm the rigidifying effect of sorgoleone. Data also suggest that mismatch in alkyl chain length between nonanoic acid or sarmentine and lipid hydrophobic tails could be responsible for bilayer destabilization. Results are discussed regarding their implications for the phytotoxicity of these compounds.